Comparative effectiveness of physical training modalities on swimming performance: a two-tier network meta-analysis - Wang, Ze; Liu, Ke; Zhao, Xinming; Gao, Jie (Frontiers in Physiology, 2025)
ObjectiveTo evaluate and compare the effectiveness of different physical training environments and modalities on swimming performance and sport-specific skills in competitive swimmers using a two-tier network meta-analysis.MethodsA systematic search of six databases identified 36 randomized controlled trials involving 844 competitive swimmers. A first-tier network meta-analysis compared aquatic, dry-land, and combined training environments across performance outcomes (25 m, 50 m, 100 m, 200 m times) and sport-specific metrics (start time, turn time, swim velocity, stroke rate, stroke length). A second-tier analysis further examined specific training modalities within combined and dry-land categories. Mean differences (MD) and standardized mean differences (SMD) with 95% confidence intervals (CI) were reported; interventions were ranked using surface under the cumulative ranking curve (SUCRA).ResultsCombined training showed the highest efficacy across multiple outcomes. Compared to control, it significantly improved 100 m time (MD = −2.01 s; 95% CI: −2.87 to −1.16), swimming velocity (MD = 1.27 m/s; 95% CI: 0.61–1.94), stroke rate (SMD = 1.63; 95% CI: 0.92–2.34), and stroke length (SMD = 0.86; 95% CI: 0.23–1.49). In the second-tier analysis, water plus dry-land resistance training (W + DRT) ranked highest across 50 m, 100 m, swim velocity, and stroke metrics. Core training and power training showed specific benefits for 25 m sprint (MD = −0.90s; 95% CI: −1.79 to −0.01) and take-off velocity (MD = 0.18 m/s; 95% CI: 0.03–0.32).ConclusionCombined aquatic and dry-land training—especially W + DRT—most effectively improves swimming performance and sport-specific skills. Core and power training function as targeted adjuncts. These findings provide a concise, precision-based prescription for physical preparation in competitive swimming.